Gestational Exposure to the Synthetic Cathinone Methylenedioxypyrovalerone Results in Reduced Maternal Care and Behavioral Alterations in Mouse Pups - Gerecsei, László I.; Csillag, András; Zachar, Gergely; Gévai, Lőrinc; Simon, László; Dobolyi, Árpád; Ádám, Ágota (Frontiers in Neuroscience, 2018)
The member of synthetic cathinone family, methylenedioxypyrovalerone (MDPV), is a frequently used psychoactive drug of abuse. The objective of our study was to determine the effect of MDPV (administered from the 8th to the 14th day of gestation) on the behavior of neonatal and adolescent mice, as well as its effect on maternal care. We measured maternal care (pup retrieval test, nest building), locomotor activity (open field test) and motor coordination (grip strength test) of dams, whereas on pups we examined locomotor activity at postnatal day 7 and day 21 (open field test) and motor coordination on day 21 (grip strength test). On fresh-frozen brain samples of the dams we examined the expression of two important peptides implicated in the regulation of maternal behavior and lactation: tuberoinfundibular peptide 39 (TIP39) mRNA in the thalamic posterior intralaminar complex, and amylin mRNA in the medial preoptic nucleus. We detected decreased birth rate and survival of offspring, and reduced maternal care in the drug-treated animals, whereas there was no difference between the motility of treated and control mothers. Locomotor activity of the pups was increased in the MDPV treated group both at 7 and 21 days of age, while motor coordination was unaffected by MDPV treatment. TIP39 and amylin were detected in their typical location but failed to show a significant difference of expression between the drug-treated and control groups. The results suggest that chronic systemic administration of the cathinone agent MDPV to pregnant mice can reduce birth rate and maternal care, and it also enhances motility (without impairment of motor coordination) of the offspring.